English Language Teachers in-Service Training: A Diagnosis Study in the Saudi Arabian Context - Mohammed, Al-Mohanna, Ayedh Dhawi (International Journal of Publication and Social Studies, 2017)
Foreign language teachers’ language competence and knowledge is one of the key factors contributing to the success of instruction as it ensures the provision of a good quality teaching. Therefore, developing this aspect of a teacher’s experience is indispensable in in-service teacher training. The present study is a critical diagnosis of in-service training programs and activities offered to English language teachers in the Kingdom of Saudi Arabia. It aims to investigate whether those teachers are satisfied with their in-service training programs and activities. English language teachers, school head teachers, and EFL educational supervisors participate in this study. To achieve the aim of the study, the researcher follows the qualitative research method where he uses the interview as an instrument for collecting data from participants. The findings of the study reveal that the EFL teachers are not satisfied with their in-service training programs and activities and that the in-service training offered to them is ineffective and does not fulfill their needs. The study also proposes some developmental recommendations and suggestions.